On Dagur Kinship Terms - Bayarma Khabtagaeva (2023)
According to conventional linguistic classifications, Dagur is one of the archaic Mongolic languages. This language is unique, allegedly connected with the Para- Mongolic language Khitan, and it has a close areal relationship with two Tungusic languages, Manchu and Solon Ewenki. This paper is a continuation of the author’s research on etymological studies of the Dagur language. Two papers have already been published, focusing respectively on names for body parts (Khabtagaeva 2021) and colours (Khabtagaeva 2022). The present paper addresses kinship terminology. The Dagur terms were collected from different published works and fieldwork materials. Most of the terms are of Mongolic origin with special Dagur phonetic features and with an internal Dagur mophological development. A few terms were borrowed from Tungusic languages and Chinese.